Age-stratified trends and outcomes of inpatient cholecystectomy for acute cholecystitis in the United States - Ayesha P. Ng; Joseph E. Hadaya; Sara Sakowitz; Zihan Gao; James Wu; Peyman Benharash (Surgery Open Science)
Background: The elderly population in the United States is rapidly expanding. Older patients over age 65 with acute cholecystitis may face greater perioperative risk compared to younger patients undergoing urgent laparoscopic cholecystectomy. We aimed to characterize trends in utilization and outcomes of inpatient cholecystectomy across the United States stratified by age. Methods: All adults undergoing nonelective, laparoscopic cholecystectomy for acute cholecystitis in the 2012–2021 National Inpatient Sample were identified. Patients were stratified into 4 age groups: 18–49, 50–64, 65–79, and 80+ years. Major adverse events included in-hospital mortality and complications. Multivariable mixed regression was used to evaluate the association of age group with outcomes. Interaction terms were used to analyze differences in risk-adjusted outcomes over time. Results: Of 2,015,699 patients, 41.7 % were aged 18–49, 24.7 % were 50–64, 23.5 % were 65–79, and 10.2 % were 80+ years. Patients aged 65–79 and 80+ had major adverse event rates of 25 % and 34 %, respectively, compared to 5–14 % among younger patients (p < 0.001). After adjustment, patients over age 65 demonstrated nearly 2-fold greater odds of major adverse events (including repair of bile duct injury) and conversion to an open operation compared to younger patients. Patients aged 65–79 comprised an increasing proportion of cholecystectomy cases over time, from 20.0 % in 2012 to 27.5 % in 2021 (p < 0.001). Conclusions: Outcomes following cholecystectomy for acute cholecystitis among older patients remained significantly worse compared to younger patients over the past decade, with complication rates of 25–34 %. Preoperative counseling about the increased risk of complications following cholecystectomy for older patients is warranted.